Estrategias metodológicas para la resolución de ejercicios de física, en el primer año de bachillerato común del colegio nacional técnico República del Perú de la ciudad de Machala, Provincia de El Oro periodo lectivo 2014 - 2015 - Torres Cruz, Vinicio Jhon (2015)
The development of this thesis Methodological strategies for solving physical exercises , in the first year of baccalaureate common national technical Republic of Peru school in the city of Machala , province of El Oro academic year 2014 - 2015.